2005
DOI: 10.1101/gr.3896805
|View full text |Cite
|
Sign up to set email alerts
|

Hotspots of mutation and breakage in dog and human chromosomes

Abstract: Sequencing of the dog genome allows an investigation of the location-dependent evolutionary processes that occurred since the common ancestor of primates and carnivores, ∼95 million years ago. We investigated variations in G+C nucleotide fraction and synonymous nucleotide substitution rates (K s ) across dog and human genomes. Our results show that dog genes located either in subtelomeric and pericentromeric regions, or in short synteny blocks, possess significantly elevated G+C fraction and K s values. Human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 61 publications
8
46
0
Order By: Relevance
“…We also observed a significant increase in divergence and GþC content in interstitial regions that are sites of syntenic breakpoints 54,56 ( Supplementary Fig. S7).…”
Section: Generating a Draft Genome Sequencementioning
confidence: 69%
See 1 more Smart Citation
“…We also observed a significant increase in divergence and GþC content in interstitial regions that are sites of syntenic breakpoints 54,56 ( Supplementary Fig. S7).…”
Section: Generating a Draft Genome Sequencementioning
confidence: 69%
“…This regional variation shows significant correlation in orthologous windows across the dog, human and mouse genomes, but the strength of the correlation seems to decrease with total branch length (pair-wise correlation for orthologous 1-Mb windows: Spearman's rho ¼ 0.49 for dog-human and 0.24 for dog-mouse comparisons). Lineage-specific variation in the regional divergence rates may be coupled with changes in factors such as sequence composition or chromosomal position 23,54 . Consistent with this, the ratios of lineage-specific divergence rates in orthologous windows are positively correlated with the ratios of current GþC content in the same windows (Spearman's rho ¼ 0.16 for dog-human, 0.24 for dog-mouse).…”
Section: Generating a Draft Genome Sequencementioning
confidence: 99%
“…Segmental duplication. In human and other eutherians, segmental duplications (defined as pairs of regions with $90% sequence similarity over $1 kb) are associated with chromosomal fragility and syntenic breakpoints 55,56 . The relative karyotypic stability of metatherians therefore indicated that they might have a low proportion of segmental duplications.…”
Section: Genome Landscapementioning
confidence: 99%
“…Hence, in a recent study, Webber and Ponting (2005) proposed the occurrence of ''hotspots'' of mutation and breakage in dog and human chromosomes.…”
Section: Discussionmentioning
confidence: 99%